Twist and turn: a revised structural view on the unpaired bubble of class II CPD photolyase in complex with damaged DNA. (2018) - Maestre-Reyna, Manuel; Yamamoto, Junpei; Huang, Wei-Cheng; Tsai, Ming-Daw; Essen, Lars-Oliver; Bessho, Yoshitaka
No abstract available